Participatory Election Oversight Socialization and Public Participation: An Implementation Analysis of Electoral Supervision in North Sulawesi - Hamdan Tahir; Goinpeace H. Tumbel; Devie S. R. Siwij (International Journal of Information Technology and Education, 2026)
This article analyzes the implementation of a participatory election oversight socialization program and its implications for public participation in election supervision in North Sulawesi. The study is positioned within public administration and policy implementation because participatory oversight is not merely a communication activity; it is an institutional intervention designed to transform citizens from passive voters into active democratic supervisors. A qualitative descriptive-analytical approach was used. Data were generated through interviews with strategic implementers, technical staff, participatory oversight cadres, and community participants, supported by observation and document analysis. The analysis applies Edward III's implementation framework, namely communication, resources, disposition, and bureaucratic structure, and connects these dimensions with supporting and inhibiting factors affecting citizen participation. The findings show that the program has been implemented through vulnerability-based regional mapping, targeted participant selection, face-to-face and online dissemination, case simulation, discussion, pre-test and post-test activities, and follow-up communication through WhatsApp groups and contact persons. Communication, disposition, and bureaucratic structure generally support implementation, but resources remain the weakest dimension because of budget limitations, archipelagic geography, uneven internet access, limited activity duration, and the insufficient readiness of citizens to prepare initial evidence for reports. The program improves electoral knowledge, awareness, consultation behavior, and initial courage to report violations, but public participation has not fully developed into strong, timely, and complete formal reporting. The article proposes an integrated model of sustainable participatory oversight based on risk-based planning, localized case simulation, cadre networks, accessible reporting channels, and continuous feedback. The study contributes to policy implementation literature by showing that citizen participation in electoral supervision requires institutional education, social trust, reporting protection, and resource-sensitive program design.